An adult case of laryngopharyngeal burn by drinking hot water. Issue 2 (13th September 2016) - Iyama, Keita; Ueki, Tomohiro; Yamano, Shuhei; Tajima, Goro; Inokuma, Takamitsu; Hirao, Tomohito; Yamashita, Kazunori; Nagatani, Atsuko; Tasaki, Osamu
Abstract : Case: A 61‐year‐old man who was hospitalized with schizophrenia in a psychiatric hospital drank hot water estimated to be 90°C. Eight hours after injury, laryngopharynx edema gradually progressed, and his breathing deteriorated. Upon arrival at our emergency room, we secured his respiratory tract by nasal intubation under a bronchoscope. Outcome: The edema gradually improved after peaking at hospital day 2, and he was extubated on hospital day 18. There were no apparent respiratory or esophageal problems, and he was discharged back to the psychiatric hospital on day 28. Conclusion: These types of laryngopharynx burns caused by ingesting hot foods or drinks have been rarely reported for adults. In cases of adults, when the patient is in a special situation such as having a psychiatric disorder, it is necessary to assume that the laryngopharynx burns might be aggravated.